2006
DOI: 10.1161/circulationaha.106.628537
|View full text |Cite
|
Sign up to set email alerts
|

Outcome After Implantation of a Cardioverter-Defibrillator in Patients With Brugada Syndrome

Abstract: Background-Brugada syndrome is an arrhythmogenic disease characterized by an increased risk of sudden cardiac death (SCD) by ventricular fibrillation. At present, an implantable cardioverter-defibrillator (ICD) is the recommended therapy in high-risk patients. This multicenter study reports the outcome of a large series of patients implanted with an ICD for Brugada syndrome. Methods and Results-All patients (nϭ220, 46Ϯ12 years, 183 male) with a type 1 Brugada ECG pattern implanted with an ICD in 14 centers bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
72
1
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(83 citation statements)
references
References 22 publications
4
72
1
6
Order By: Relevance
“…However, we also observed syncope in one patient with an implantable loop recorder with no documented ventricular arrhythmias. A multicentre study (17) recently reported on a large series of patients with BS implanted with ICDs, and the results were in accordance with the present findings. In the study (17), device interrogation showed no ventricular arrhythmia in 10% of the recurrent syncopal spells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, we also observed syncope in one patient with an implantable loop recorder with no documented ventricular arrhythmias. A multicentre study (17) recently reported on a large series of patients with BS implanted with ICDs, and the results were in accordance with the present findings. In the study (17), device interrogation showed no ventricular arrhythmia in 10% of the recurrent syncopal spells.…”
Section: Discussionsupporting
confidence: 93%
“…A multicentre study (17) recently reported on a large series of patients with BS implanted with ICDs, and the results were in accordance with the present findings. In the study (17), device interrogation showed no ventricular arrhythmia in 10% of the recurrent syncopal spells. ICD implantation in an asymptomatic population with a positive EPS was based on the report of the second consensus conference on BS (3) and on the Brugada brothers' studies (10,12,13).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Sacher, et al found inappropriate shocks to be 2.5 times more common than appropriate shocks. 13) Thus, the arrhythmogenic substrate in Brugada syndrome may not be restricted to the ventricular level; similar changes may occur in the atria and could be the substrate for re-entrant atrial tachyarrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Incidences of spontaneous atrial arrhythmias between 0% and 53% have been reported, [7][8][9][10][11][12][13][14][15][16][17][18] although the inducibility of atrial arrhythmia ranges from 3% to 100%. [7][8][9][10][11][12][13][14][15][16][17][18] Little is known about the relation between atrial arrhythmias and electrophysiologic backgrounds. We therefore compared depolarization and repolarization properties of the atria between patients with Brugada syndrome and control patients who underwent catheter ablation for tachyarrhythmias.…”
mentioning
confidence: 99%